Higher Interest Rate & Credit Risk Management: Insights for Pakistan’s Banking Sector from Us Silicon Valley Bank - Saleem, Munazza; Masood, Omar (iRASD Journal of Economics, 2023)
This paper examines the latest interest rate trends and credit risk management for the performance of Pakistan’s banking industry and drawing lessons from the default of Silicon Valley Bank. In the ever-evolving landscape of the banking industry, the delicate balance between interest rates and credit risk management emerges as a pivotal force shaping the sector's performance. This research provides a roadmap for financial institutions to harness the moderating influence of interest rates on credit risk, ultimately enhancing performance and resilience. Pakistan's banking industry must learn from the experiences and apply them to their own risk management practices. The study emphasizes the need for enhanced risk assessment frameworks, including thorough borrower evaluation, stress testing, and scenario analysis. It was conducted by well-structured questionnaire from a sample of 230 seasoned, experienced employees of top ten banks of Pakistan. The results of multiple regression showed that three variables: Credit Risk Management (CRM hereafter), Bank Performance and Interest rate are interconnected, statistically significant, affect each other and interest rate contribute in performance and strengthen CRM techniques. The study is quite useful for understanding and comprehending the changes in Pakistan’s banking industry over the past and in the latest scenarios of higher interest rates. Future contribution will be that this research will supply the foundation for other researchers who wish to dig into monetary policies and related disciplines.